E-Mobility as a sustainable system innovation. Insights from a captured niche. - Augenstein, Karoline (Shaker, 2015)
In der Arbeit beschäftigt sich die Autorin mit der Frage, ob die aktuellen Entwicklungen im Bereich der Elektromobilität das Potenzial haben, zu einer nachhaltigen Transformation des Mobilitätssektors beizutragen. Sie führt aus, warum eine rein quantitative Diffusion von E-Fahrzeugen noch lange keine nachhaltige Mobilitätswende ausmacht und was es für diese bedarf. Sie plädiert für eine ganzheitlichere Vision nachhaltiger Elektromobilität - eine Systeminnovation. Die zentrale Fragestellung der Arbeit lautet: Wie können wir, in der jetzigen frühen und kritischen Phase, feststellen, wie groß das Potenzial ist, dass sich Elektromobilität als eine nachhaltige Systeminnovation entwickelt? Um diese Frage zu beantworten, wird zunächst ein analytisches Rahmenkonzept entwickelt, basierend auf der "Multi-Level Perspektive" nachhaltiger Transformationsprozesse und unter Einbeziehung der Konzepte der transformativen Kapazität neuer Technologien und der Systemadaptivität.

In 2009, the German government launched its "National Development Plan for Electric Mobility" which set the concrete target of having 1 million electric vehicles on the road by 2020. However, there have been hypes around e-mobility before and even if this goal were to be reached, a merely quantitative aim of a certain number of electric vehicles will not suffice to contribute to a more sustainable development in transport. This requires a more comprehensive vision of sustainable e-mobility as a system innovation. Thus, the question addressed in this thesis is: How can we assess - at this critical early stage - whether there is potential for e-mobility developing as a sustainable system innovation? A theoretical framework will be developed for assessing the potential of a wider transition at an early stage by analyzing current patterns of socio-technical co-evolution and embedding these in a wider framework of the structural dynamics involved in transitions. The aim of the analysis is to identify whether "system-innovative" projects do emerge in the case of Germany/Baden-Württemberg and what patterns (e.g. in terms of specific actor constellations, institutional adjustments etc.) can explain this. It will be shown that the system-innovative potential of this e-mobility niche remains limited, due to the powerful influence of incumbents, conflicting political goals and traditional science approaches. A few more system-innovative activities emerge where powerful actors from outside are involved, who are capable of viewing mobility in a more systemic way (e.g. actors from the public transport or housing sector). It is argued that the role of large demonstration projects is important, but they need to be designed as transdisciplinary research projects from the beginning.
Keywords: Verkehr; Verkehrspolitik; Mobilität; Innovation; Marktentwicklung; Fahrzeug; Forschung; Elektroantrieb; Entwicklungsplanung; Zielkonflikt; Elektromobilität; Energiewende; Nachhaltigkeit; Transformation; Modellregion; Interdisziplinarität; Rahmenbedingung